SpringerLink Header: Imaging (T. Lang, F. Wehrli, Section Editors) To appear in Volume 16, Issue 6, December 2018 - Yoder, James S. (Curr Osteoporos Rep, 2018)
PURPOSE OF REVIEW: This review article attempts to summarize the current state and applications of the hybrid imaging modality of PET-MRI to metabolic bone diseases. The advances of PET and MRI are also discussed for metabolic bone diseases as potentially applied via PET-MRI. B) RECENT FINDINGS: Etiologies and mechanisms of metabolic bone disease can be complex where molecular changes precede structural changes. Although PET-MRI has yet to be applied directly to metabolic bone disease, possible applications exist since PET, specifically (18)F-NaF PET, can quantitatively track changes in bone metabolism and is useful for assessing treatment, while MRI can give detailed information on bone water concentration, porosity, and architecture through novel techniques such as UTE and ZTE MRI. C) SUMMARY: Earlier detection and further understanding of metabolic bone disease via PET and MRI could lead to better treatment and prevention. More research using this modality is needed to further understand how it can be implemented in this realm.